Penggunaan Flashcard Game dalam Penerapan Cognitive Behaviour Therapy (CBT) Pada Pasien Skizofrenia dengan Masalah Harga Diri Rendah - Sri Maryatun; Zulian Effendy; Sayang Ajeng Mardhiyah (Jurnal Kesehatan, 2021)
Low self-esteem is one of the negative symptoms experienced by schizophrenia patients. A person evaluates himself as low, not good, always fails, is useless to become a burden and stressor for others in an extended period without any support or support system from the environment, raises the risk of suicide. This situation is a serious concern for all parties, especially health workers to be able to provide comprehensive and effective mental nursing care management, namely Cognitive Behaviour Therapy (CBT). This study was aimed to determine the effectiveness of CBT with flashcards on changes in signs and symptoms of low self-esteem in schizophrenic patients. Group therapy based on Cognitive Behavior Therapy (CBT) with flashcard media is one of the development and innovation models of psychotherapy that has an impact on increasing self-esteem in schizophrenia patients because the flashcard method makes it easier for patients to find positive thoughts in the form of communicative and interactive games so that patients feel their self-esteem increases and can behave adaptively. The research design was used a quasi-experimental pre-posttest with a control group. A sample of 50 people includes 25 people in the intervention group and 25 people in the control group. The results were showed that the reduction in signs and symptoms of low self-esteem in schizophrenic patients was greater in the intervention group than in the control group (p-value≤0,05). CBT therapy with flashcards was effective in reducing low self-esteem by 65,6%. CBT therapy with flashcards is recommended as an effective, efficient, and easy therapy for health workers and families to increase self-esteem for clients.